2015
DOI: 10.17554/j.issn.2311-5106.2015.02.91
|View full text |Cite
|
Sign up to set email alerts
|

Knee Joint Distraction as an Alternative Surgical Treatment for Osteoarthritis: Rationale and Design of two Randomized Controlled Trials (vs High Tibial Osteotomy and Total Knee Prosthesis)

Abstract: AIM:In case of refractory knee osteoarthritis at a relatively young age causing persisting pain, treatment options are limited. In case of medial degeneration high tibial osteotomy (HTO) may be considered, or in case of more generalized OA, a total knee prosthesis (TKP). However, these young and active patients have a major risk of revision surgery. Knee joint distraction (KJD) could be an alternative treatment; prolonged clinical benefit and cartilage tissue repair have been demonstrated. Therefore, two RCTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…A sample size calculation was performed for the primary RCT. 24 For the present study, a convenience sample was used, aiming for a response rate >80%. Demographic data, and preand postoperative sport and work participation were analyzed using descriptive statistics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample size calculation was performed for the primary RCT. 24 For the present study, a convenience sample was used, aiming for a response rate >80%. Demographic data, and preand postoperative sport and work participation were analyzed using descriptive statistics.…”
Section: Discussionmentioning
confidence: 99%
“…With KJD, an external distraction device creates a temporary load reduction between focal areas of cartilage surfaces in the knee. 24 Intema et al showed that KJD treatment resulted in radiographic improvement of joint space width (JSW) and increased cartilage thickness on MRI, indicative of tissue structure modification that may have beneficial effects on patients' knee pain and symptoms. 25 A preserved treatment effect up to 5 years has been described with increased minimum JSW at 5-year post-treatment compared with pretreatment.…”
mentioning
confidence: 99%
“…Recently, 42 patients have been treated with KJD in 2 randomized controlled trials comparing KJD with high tibial osteotomy and with TKA. 26 Based on such numbers a prediction of failure to KJD might be found in the future. However, in over a 110 patients treated with joint distraction in case of ankle osteoarthritis only female gender appeared predictive of failure.…”
Section: Discussionmentioning
confidence: 99%
“…All inclusion aspects have been described in detail for all three studies, previously. [8,13,14,16] All trials were granted ethical approval by the medical ethical review committee of the University Medical Center Utrecht (protocol numbers 04/ 086, 10/359/E, and 11/072) and registered in the Netherlands Trial Register (trial numbers NL419, NL2761 and NL2680). All patients gave written informed consent.…”
Section: Patientsmentioning
confidence: 99%